Pencegahan Fraud : Pengaruh Whistleblowing System, Government Governance dan Kompetensi Aparatur Pemerintah - Inawati, Wahdan Arum; Sabila, Fadiyah Hani (E-Jurnal Akuntansi, 2021)
This study examines the prevention of fraud in central and local government agencies by looking at the whistleblowing system, government governance, and the competence of government officials. Researcher used mix method technique, combined quantitative and qualitative. This type of quantitative data uses a questionnaire or questionnaire distributed to the State Civil Apparatus (ASN) of the central and local governments as many as 50 people. Meanwhile, for qualitative data, in-depth interviews will be conducted with 5 respondents who have filled out the questionnaire. The data collection technique in this study was a questionnaire with an ordinal scale, namely a Likert scale. Based on the results of statistical tests, it can be concluded that government governance and the competence of government officials have a positive effect on fraud prevention. Meanwhile, the whistleblowing system has no effect on fraud prevention. Keywords: Competence Of Government Officials; Fraud Prevention; Government Governance; Whistleblowing System.